Shinsei: a madeira na arquitectura religiosa japonesa - Stéphanie das Neves Bastos (2017)
This work was elaborated with the desire of exploring and understandingJapanese religious architecture, as well as displaying it in a way that exalts itsmysticism, inventiveness and beauty. Here, religious architecture will be specificallyexplained through the analysis of historical periods and important milestones, aswell as society's development from those factors.The uncontrollable forces of nature shaped constructive culture, revealing howephemeral buildings were when subjected to earthquakes, tsunamis, hurricanes,typhoons, et cetera. They directed society towards the adaptation to and worshipof natural forces that manifested in architecture through structures where crossbracingwas barely present, but was compensated for using bracket systems thatprovide flexibility to the structure, which is going to be essential for resisting severeweather conditions and seismic shocks.The worship of nature developed the indigenous religion Shintō which manifestedthrough exclusive use of raw materials provided by nature itself, especially wood.There is a fondness for natural features, for organic forms and layouts that dominateJapan's rugged territory and that only finds rationalization when continentalcultures start invading the archipelago with Buddhism.Because the new religion was equally based on nature, it allowed the peacefulsyncretism between Shintō and Buddhism. New construction styles were introduced,as well as a new aesthetic exchange between Buddhist temples and Shintō shrines(with the use of Buddhist elements in Shintō shrines and vice-versa) and alsoterritorially speaking (through the sharing of holy grounds between temples andshrines).Therefore, the main theme here will be the study of Japan's religious architecture,namely Buddhist temples and Shintō shrines, keeping in mind the use of wood asthe main raw material and its ability to withstand abuse from the natural elementsto which its territory is constantly subjected to.